vdmR: Generating Web-Based Visual Data Mining Tools with R - Fujino, Tomokazu (Journal of Statistical Software, 2017)
The vdmR package generates web-based visual data mining tools by adding interactive functions to ggplot2 graphics. Brushing and linking between multiple plots is one of the main features of this package. Currently, scatter plots, histograms, parallel coordinate plots, and choropleth maps are supported in the vdmR package. In addition, identification on a plot is supported by linking the plot and the data table.